FAKTOR-FAKTOR PENGOLAHAN YANG MEMENGARUHI MUTU ORGANOLEPTIK KERUPUK CUMI-CUMI - Filardi, Tara; Rusky I. Pratama; Yuli Andriani; Iis Rostini (TECHNO-FISH, 2025)
Squid (Loligo sp.) is a non-fish fishery product that has high economic value and abundant nutritional content, especially protein, fat, and minerals. The utilization of squid as raw material for crackers is a food product diversification innovation that can increase the added value of this commodity, especially in the micro, small and medium enterprise (MSME) sector. This study aims to systematically review the biological classification of squid, its nutritional content, the process of making squid crackers, and factors that affect the organoleptic quality of the product. This article uses a literature review approach to review the factors in the manufacturing process that affect the quality of squid crackers, including the squid cracker manufacturing process involving the stages of washing and weeding, mashing, dough making, dough molding, dough steaming, cracker drying, and cracker frying. The study results show that the quality of squid crackers is highly influenced by the quality of raw materials, dough kneading, dough steaming time, dough drying, and frying temperature determine the final product.